RANGE OF DISTRIBUTION COST ITEMS IN VIEW OF BUSINESS PROCESS MERCHANDISE SYSTEMS - Natalya A. Rumachik; Alla G. Chernova (Вестник Северо-Кавказского федерального университета, 2022)
The article reveals an approach to cost accounting in a trade organization based on the construction of a range of distribution cost items in the context of the five selected business processes: business process of supply; business-process of storage; business-process of selling; business-process of “Marketing Research”; business-process “Management and control”, which would allow taking into maximum account all the costs incurred both by the organization as a whole, and by structural units responsible for individual business processes.